LOCAL WISDOM OF INDONESIA: REVITALIZATION IN PHILOSOPHICAL BASIS ON INDONESIAN CRIMINAL PUNISHMENT PURPOSE - Mahmud Mulyadi (USU Journal of Legal Studies, 2017)
The philosophy of criminal punishment purpose in Indonesia which is used until today, is based on the criminal punishment purpose brought by Dutch Colonial, both for retributive, deterrence, or integrative purpose. Indeed, this philosophy must be improved, since it may have not been adjusted with Indonesian values. Because of that, another digging in criminal punishment purpose in Indonesian vibe based on local wisdom is necessary. This digging of local wisdom in criminal punishment scope will make Indonesian criminal punishment concept rich and highly valued in law enforcement. By that, law protection based on the purpose of law to create legal certainty, legal justice, and legal expediency is desired.